An optimal analysis for Darcy–Forchheimer three-dimensional Williamson nanofluid flow over a stretching surface with convective conditions. (March 2019) - Dawar, Abdullah; Shah, Zahir; Islam, Saeed; Khan, Waris; Idrees, Muhammad
The augmented thermal conductivity is significant in betterment of heat transfer behavior of fluids. A number of other physical quantities such as density, viscosity, and specific heat play the key role in fluid flow behavior. Investigators have shown that the nanofluids have not only superior heat conductivity but also have better convective heat transfer capability than the base fluids. In this article, the analysis of three-dimensional Williamson fluid has been carried out under investigation. The fluid flow is taken over a linear porous stretching sheet under the influence of thermal radiation. The transformed system of equations has been solved by homotopy analysis method. The impact of embedded parameters on the fluid flow has shown graphically. The velocity profile in x-direction is decreased with the augmented stretching, Williamson, coefficient of inertia, and porosity parameters. The velocity profile in y-direction is increased with the enlarged stretching parameter, while reduced with the augmented Williamson, coefficient of inertia, and porosity parameters. The temperature profile is increased with the enlarged stretching, radiation, thermophoresis, parameter and Brownian motion parameters, and Biot number while decreased with the increased Prandtl number. The concentration profile is increased with the increased thermophoresis parameter and Biot numbers, while decreased with the enlarged stretching and Brownian motion parameters.